Dermoscopic And Clinical Features Of Alopecia Areata In Pakistani Patients: A Cross-Sectional Study - Ahmed, Mahwish; Ayub, Neelam; Hamza, Muhammad; Nafisa, Asma; Zaidi, Dua Zhaira; Zaidi, Ismat Zhaira (Journal of Rawalpindi Medical College, 2025)
Objective: To evaluate the dermoscopic and clinical findings in Pakistani patients with Alopecia Areata Methods: The study was conducted at THQ Hospital Layyah with a sample size 800 within an age limit of 10-40. The patient's clinical history and demographic information were collected using a structured interviewing questionnaire with informed consent. Patients were examined using a Dermlite dermoscope. Results: Of 800 patients, 52.9% were females and 47.1% were malesThe scalp was the most common site of alopecia among the studied patients, accounting for 89.9% (n=719). Dermoscopy of AA patients revealed the following: yellow dots in 79.9% (n=559), black dots in 33.1% (n=265), exclamation mark hairs in 42.5% (n=340), short villus hairs in 32.6% (n=261), broken hairs in 42.3% (n=338), pigtail hairs in 27.9% (n=223), and Pohl-Pinkus constriction in 25.9% (n=207). The Pearson chi-square test showed a significant correlation between age and the presence of black dots, yellow dots, broken hairs, exclamation mark hairs, pigtail hairs, short villus hairs, and Pohl-Pinkus constriction (p < 0.001). Conclusion: Alopecia Areata affects both men and women equally. The majority of affected individuals are young, between the ages of 10 and 30. The scalp is the typical site of Alopecia Areata. Key Words: Alopecia.